Design, rationale, and initiation of the Surgical Interventions for Moderate Ischemic Mitral Regurgitation Trial: A report from the Cardiothoracic Surgical Trials Network - Smith, Peter K.; Michler, Robert E.; Woo, Y. Joseph; Alexander, John H.; Puskas, John D.; Parides, Michael K.; Hahn, Rebecca T.; Williams, Judson B.; Dent, John M.; Ferguson, T. Bruce; Moquete, Ellen; Rose, Eric A.; et al. (The Journal of thoracic and cardiovascular surgery, 2012)
Patients with coronary artery disease complicated by moderate ischemic mitral regurgitation have demonstrably poorer outcome than do patients with coronary artery disease but without mitral regurgitation. The optimal treatment of this condition has become increasingly controversial, and a randomized trial evaluating current practices is warranted. We describe the design and initial execution of the Cardiothoracic Surgical Trials Network Surgical Interventions for Moderate Ischemic Mitral Regurgitation Trial. This is an ongoing prospective, multicenter, randomized, controlled clinical trial designed to test the safety and efficacy of mitral repair in addition to coronary artery bypass grafting in the treatment of moderate ischemic mitral regurgitation. The results of the Cardiothoracic Surgical Trials Network Surgical Interventions for Moderate Ischemic Mitral Regurgitation Trial will provide long-awaited information on controversial therapies for this morbid disease process.